2016
DOI: 10.1007/s12199-016-0577-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of smoking status with other lifestyle behaviors are modified by sex and occupational category among urban civil servants in Japan

Abstract: Objectives The aim of the present study was to examine the associations of current smoking with five other unhealthy lifestyle behaviors among urban civil servants in Japan according to sex and occupational category. Methods The study included 10,232 urban civil servants in Japan who presented for a health check-up in 2011. We analyzed data on anthropometric measurements and selfreported lifestyle factors. Results Current smokers had a higher BMI than never smokers in white-collar workers, but not in blue-coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…42 Another reason for a high rate of smoking in manual workers may be their hard physical tasks or a common practice of smoking at their workplace. 21,43 However, in this study, after mutual adjustment for education, only men aged 20-64 had a finding consistent with previous studies: manual workers were more likely to be current smokers than upper non-manual workers. For women, among those aged ≥65, upper non-manual workers had a significantly higher current smoking prevalence than manual workers.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…42 Another reason for a high rate of smoking in manual workers may be their hard physical tasks or a common practice of smoking at their workplace. 21,43 However, in this study, after mutual adjustment for education, only men aged 20-64 had a finding consistent with previous studies: manual workers were more likely to be current smokers than upper non-manual workers. For women, among those aged ≥65, upper non-manual workers had a significantly higher current smoking prevalence than manual workers.…”
Section: Discussionsupporting
confidence: 91%
“…41 For the association between occupation and smoking, many studies have reported a significant association between lower level occupations and a higher percentage of current smokers. 13,[19][20][21][22][23][24] It is well known that people with lower level occupations have more difficulties in successfully quitting smoking than those with higher level occupations because they are less likely to receive treatment and support to quit. 42 Another reason for a high rate of smoking in manual workers may be their hard physical tasks or a common practice of smoking at their workplace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The motivation to quit only appears to play a crucial role in predicting quit attempts (Smits et al, 2016), but not the final outcome. Consequently, other psychological factors other than motivation need to be investigated as shown by a number of studies (Higashibata, Wakai, Okada, Nakagawa & Hamajima, 2016;Masiero, Riva, Oliveri, Fioretti & Pravettoni, 2018;Yong et al, 2018).…”
Section: Psychological and Behavioral Correlates Of Readiness To Stop Smokingmentioning
confidence: 99%